Pengaruh Pelapisan Kaolin Pada Titanium Dioksida (TiO2) dan Zinc Oksida (ZnO) Terhadap Aktivitas Fotokatalitik Lapisan Tipis - Okta Khairina; Riri Jonuarti (Journal of Science, Technology, and Innovation, 2026)
Titanium dioxide (TiO₂) and zinc oxide (ZnO) are widely applied as broad-spectrum ultraviolet protective agents; however, nanoscale modification that improves optical transparency may simultaneously increase photocatalytic activity and reactive oxygen species (ROS) generation. This study investigated the effect of kaolin coating on the photocatalytic behavior of TiO₂ and ZnO thin films fabricated through spin coating. Nanoparticles were reduced to sizes below 150 nm using high-energy ball milling and deposited into sandwich-structured nano-kaolin/TiO₂ and nano-kaolin/ZnO films with weight ratios of 0%:100% and 50%:50%. Photocatalytic performance was evaluated through methylene blue degradation under ultraviolet irradiation for 5 h at 664 nm. Pure TiO₂ and ZnO exhibited high photocatalytic degradation efficiencies of 72.77% and 68.51%, respectively. Incorporation of 50% kaolin significantly reduced degradation efficiencies to 22.10% for TiO₂/kaolin and 23.69% for ZnO/kaolin. Kaolin contributed to initial physical adsorption while suppressing ROS formation through active-site coverage and controlled charge-transfer pathways. The resulting sandwich-structured thin films demonstrated improved optical stability, reduced photocatalytic aggressiveness, and promising potential as multifunctional UV-protective nanomaterials for safer sunscreen-related applications.